Distributed decisions on TV spectrum allocation considering spatial and temporal variation - Chen, Zhenwei (2018)
TV spectrum has lower path loss, longer transmission range, and higher penetration capability, resulting in a wide range of potential important applications. However, unlike Wi-Fi bands, TV spectrum is subjected to high spatial and temporal variations due to the random arrivals and departures of primary users (PUs), which results in new technical challenges in TV spectrum utilization. One important issue is how to allocate TV spectrum to secondary users (SUs) by taking the spatial and temporal variations into consideration. This has been largely ignored in previous studies. In this paper, we first formulate the TV spectrum allocation problem as a 0–1 integer optimization problem, and then we approximate our optimal objective via Log-Sum-Exp function. Thereafter, we solve this problem by implementing a Markov chain in a distributed manner. Furthermore, we extend the static problem setting to a dynamic environment where the number of vacant TV channels varies with time due to the arrivals and departures of PUs. Simulation results show that our proposed distributed algorithm can converge very fast to the optimal solution, and can achieve a close-to optimal performance with a guaranteed loss bound.